Identification and antimicrobial susceptibility of Staphylococcus from home-treated peritoneal dialysis patients - Batalha, J. E. N. [UNESP]; Cunha, M. L. R. S. [UNESP]; Montelli, A. C. [UNESP]; Barretti, Pasqual [UNESP]; Caramori, Jacqueline Socorro Costa Teixeira [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2010)
Staphylococcus aureus is the main agent of infections during peritoneal dialysis (PD). The presence of S. aureus in the nasal cavity has been extensively studied and suggested as a risk factor of dialysis-related infections, whereas coagulase-negative Staphylococcus (CNS) species are frequently considered part of the normal human microbiota. The aim of this study was to identify Staphylococcus in the nasal cavity, pericatheter skin and peritoneal effluent from PD patients, as well as to evaluate the antimicrobial activity evolution in vitro. Thirty-two chronic PD patients were observed during 12 months and had nasal and pericatheter skin samples collected for culture. When peritonitis was detected, samples were also collected from the peritoneal effluent for culture. The activity of several antimicrobial drugs (penicillin G, oxacillin, cephalothin, ofloxacin, netilmicin and vancomycin) against different Staphylococcus species was measured by using the agar drug diffusion assay (Kirby-Bauer method). Staphylococcus was separated into S. aureus, S. epidermidis and other CNS species in order to determine the in vitro resistance level. S. epidermidis resistance to oxacillin progressively increased during the study period (p < 0.05). Resistance to ofloxacin was inexpressive, whereas resistance to netilmicin and vancomycin was not detected. of the oxacillin-resistant species (n = 74), 83% were S. epidermidis, 13% other CNS and 4% S. aureus (p < 0.05). Regarding multidrug resistant strains (n = 45), 82% were S. epidermidis, 13% other CNS, and 5% S. aureus (p < 0.05). This study shows the relevance of resistance to oxacillin and CNS multi-drug resistance, particularly concerning S. epidermidis, in PD patients.
Keywords: peritoneal dialysis (PD); peritonitis; risk factor; Staphylococcus; coagulase-negative Staphylococcus (CNS)